Usability Efficiency Analysis on E-Learning Websites - Listriana Kusumastuti, Dwi; ., Sasmoko; Harna Yossy, Emny; Ghadati Rucia, Sanna; Indrianti, Yasinta (International Journal of Engineering and Technology, 2018)
The challenge of website-based information technology is how to channel information globally quickly and precisely. The goal is that the website is not still visited by visitors, especially for e-learning website. But many challenges for e-learning service administrators. E-learning website should provide good usability, so that interaction with learners can be done quickly and precisely. The purpose of this study is to analyze the efficiency level of usability on e-learning website in case of sasmoko.com by using Nielsen model. Data analysis was carried out using the descriptive analysis technique and the next percentage was assessed for the efficiency criteria. The results of the analysis proved to improve usability on sasmoko.com site, so it can support lectures of Research Methods as blended learning.Â